1989
DOI: 10.1073/pnas.86.5.1500
|View full text |Cite
|
Sign up to set email alerts
|

jun-D: a third member of the jun gene family.

Abstract: The protooncogene c-jun encodes a component of the transcription factor AP-1. Both murine c-jun and a related gene (jun-B) are rapidly activated in BALB/c3T3 cells by serum growth factors. We report here the cloning and analysis of a cDNA encoding a third member of the murine jun family, jun-D. The amino acid sequence encoded by jun-D has two extensive regions of homology with the other Jun proteins. One homology region includes the DNA-binding domain and sequences required for dimer formation and interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
190
0
1

Year Published

1996
1996
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 398 publications
(198 citation statements)
references
References 28 publications
6
190
0
1
Order By: Relevance
“…EGF-induced junD transcripts were detectable up to 2 h, at a similar level to that seen after 30 min stimulation. Co-treatment with SB 203580 resulted in slightly higher junD mRNA accumulation and this approximately 1.5-fold increased level was maintained over the full timecourse analysed here; this is possibly due to the intrinsic stability of these transcripts compared to that of other IE genes (Ryder et al, 1989;CAH and LCM not shown). Although elevated, the enhanced induction responses seen here were considerably lower than those observed under superinducing conditions with anisomycin (data not shown).…”
Section: Analysis Of Mrna Stability In Sb 203580-treated Egfstimulatementioning
confidence: 61%
See 1 more Smart Citation
“…EGF-induced junD transcripts were detectable up to 2 h, at a similar level to that seen after 30 min stimulation. Co-treatment with SB 203580 resulted in slightly higher junD mRNA accumulation and this approximately 1.5-fold increased level was maintained over the full timecourse analysed here; this is possibly due to the intrinsic stability of these transcripts compared to that of other IE genes (Ryder et al, 1989;CAH and LCM not shown). Although elevated, the enhanced induction responses seen here were considerably lower than those observed under superinducing conditions with anisomycin (data not shown).…”
Section: Analysis Of Mrna Stability In Sb 203580-treated Egfstimulatementioning
confidence: 61%
“…Note that induction of the fosB gene in response to anisomycin is generally extremely weak or undetectable. Inhibition of junD by SB 203580 is less apparent than that of c-fos, c-jun or junB; this may be due to the increased stability and persistence of these transcripts compared to that of the other IE genes studied here (Ryder et al, 1989; CAH and LCM not shown; see Figure 5). These results correlate well with the dose-dependence of inhibition of MAPKAP-K2 activation by SB 203580 in C3H 10T cells (Hazzalin et al, 1996;EC and LCM, unpublished data).…”
Section: Erksmentioning
confidence: 78%
“…Wild type c-Jun and mutants cloned into either RSV-or CMV-based eukaryotic expression vectors have been previously described: c-Jun/CMV (Brown et al, 1996); c-Jun/RSV ; JunD287 ± 331 (Alani et al, 1991); the leucine zipper point mutants, M8, M9 and M14, ; internal deletion mutants, JunD194 ± 223 and JunD146 ± 221 ; JunA?D 265 In265 (Brown et al, 1996); c-Jun/v-Jun chimeras (Oehler et al, 1993); and cJun Ala63/73 (Smeal et al, 1991). JunB (Schutte et al, 1989) and JunD (Ryder et al, 1989) have been previously described. JunD1 ± 245 was constructed by using the polymerase chain reaction (PCR) to amplify c-Jun amino acids 246 ± 331.…”
Section: Plasmidsmentioning
confidence: 99%
“…The jun and fos families of genes are composed of three jun members (c-jun, junB, and junD) (Bohmann et al, 1987;Hirai et al, 1989;Maki et al, 1987;Ryder et al, , 1989 and four di erent fos partners (c-fos, fosB, fra1 and fra2) (Cohen and Curran, 1988;Nishina et al, 1990;Zerial et al, 1989). These genes encode components of the AP1 transcription factor formed by homo-or hetero-dimerization of the Jun and Fos proteins.…”
Section: Introductionmentioning
confidence: 99%